Visual Narrative in a Single Frame: A Semiotic Analysis of the Makmum (2019) Film Poster as a Communication of Horror Aesthetics - Muhamad Ilham; Mahendradewa Suminto; Mohammad Rezaie (Jurnal Lingua Idea, 2026)
The Indonesian horror film Makmum (2019) gained critical and popular attention for its distinctive approach to horror, emphasizing psychological tension and spiritual unease over conventional jump scares. As part of its visual communication strategy, the film’s official poster plays a crucial role in conveying its aesthetic and thematic essence. This study applies Roland Barthes’ semiotic theory of denotation, connotation, and myth to analyze how the poster functions as a visual narrative within a single frame, encapsulating the film’s horror aesthetics. Using a qualitative semiotic method, the poster is examined through its core visual elements: composition, lighting, typography, and symbolism. The findings reveal that the poster’s minimalist design and stark contrast lighting effectively evoke the film’s oppressive atmosphere. The central composition, featuring a veiled woman in prayer and a shadowy figure behind her, mirrors the mise-en-scène of spiritual vulnerability and unseen terror. Religious symbols such as the mukena are recontextualized, shifting their connotative meaning from sanctity to threat, thereby constructing a myth of spiritual disturbance rooted in local cultural beliefs. This visual strategy not only reflects the film’s narrative but also prepares the audience psychologically for its thematic depth. The poster becomes more than promotional material; it acts as a semiotic gateway into the film’s emotional and cultural landscape. Thus, the graphic design serves as an extension of the cinematic experience, reinforcing the psychological and spiritual horror embedded in the story.